1994
DOI: 10.1002/jsfa.2740650218
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of beer foam polypeptides by hydrophobic interaction chromatography and their partial characterisation

Abstract: Beer foam polypeptides have been separated into five groups based on their relative hydrophobicity. Foam stability increases with increasing hydrophobicity of the polypeptide groups. The most hydrophobic polypeptide group contains a large proportion of Coomassie blue-binding polypeptides. Analysis by SDS-PAGE reveals that each polypeptide group is composed of several differently-sized polypeptides. Further purification by anion-exchange chromatography results in five fractions, each of which has a different po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 27 publications
5
38
0
1
Order By: Relevance
“…protein is present in these fractions, it must be the result of recombination of smaller proteins and/or peptides by sulfhydryl bonding, as referred to earlier, or by hydrophobic interactions. The electrophoretic picture presented here is very similar to those reported earlier by other researchers using similar conditions 9,14,15,29 . There is full agreement that beer proteins are mostly constituted by peptides of less than 20 × 10 3 mol.…”
Section: )79087 %2( (-7'977-32supporting
confidence: 90%
See 1 more Smart Citation
“…protein is present in these fractions, it must be the result of recombination of smaller proteins and/or peptides by sulfhydryl bonding, as referred to earlier, or by hydrophobic interactions. The electrophoretic picture presented here is very similar to those reported earlier by other researchers using similar conditions 9,14,15,29 . There is full agreement that beer proteins are mostly constituted by peptides of less than 20 × 10 3 mol.…”
Section: )79087 %2( (-7'977-32supporting
confidence: 90%
“…Among the latter group, there are some important proteins, especially for foam formation and retention, such as the lipid transferring protein 6 (LTP1) with molecular weight of about 9,000 Da. It is pertinent to note that other researchers also reported the separation of beer proteins into only four or five fractions using hydrophobic interaction chromatography 9,14,15,26,29 . This means that the hydrophobic techniques exclude the hydrophilic peptides leaving a gap in the comprehensive knowledge and understanding of the role of proteins and peptides in wort and beer.…”
Section: )79087 %2( (-7'977-32mentioning
confidence: 99%
“…The major proteins associated with beer foam formation and stability are protein Z, a barley protein with a molecular weight of 40 kD 13 , a 17 kDa protein 27 and Lipid Transfer Protein 1 (LTP1) 5,12,25 . It has been widely accepted that it is the property of the polypeptide hydrophobicity rather than size of the polypeptide that is important in giving a stable foam 21,24 . LTP1 has been found to constitute up to 40% of the protein content of the foam fraction.…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…Slack and Bamforth 17 measured hydrophobicity and suggested that polypeptides can uncoil their structure to reveal more hydrophobic regions which results in a more stable foam. Onishi and Proudlove 16 isolated beer fractions of increased hydrophobicity that appeared to have identical polypeptide composition. Bamforth 4 showed there was a correlation between hydrophobic protein and foam stability.…”
mentioning
confidence: 99%